Structural modelling of riparian tree diversity and ecosystem degradation roles in determining the water quality of springs and its drains in East Java - Chatarina Gradict Semiun; Catur Retnaningdyah; Endang Arisoesilaningsih (Brawijaya University, 2020)
This research was aimed to study the role of riparian trees and ecosystem degradation to determine water quality in some springs and its channels located in East Java. The research was held in some selected degraded springs in Kediri, Pasuruan, Malang, and the Meru Betiri National Park located in Jember, as a reference site. In each spring, three sites including upstream, midstream, and downstream were observed. The field observation consisted of several steps such as land use quality at river land side, geographical conditions, riparian tree diversity and water quality, quality of springs physical condition, and its channels. Riparian trees role to determine the water quality was analyzed by applying Partial Least Square analysis with Smart PLS software. Structural modelling of the interaction of riparian trees diversity with some determining variables of water quality revealed that there was an important role of riparian diversity quality towards water quality. The value of predictive relevance (Q2) was 99.11% and the model could be accepted. The riparian trees diversity and geographical conditions directly influenced the water colour and its turbidity. The quality of land use at several water bodies did not directly influence the water colour and its turbidity. Therefore, water colour and its transparency at channels were directly influenced by riparian width, ecosystem degradation shown by naturalness index, hemeroby index, environmental services index, and the slope of landside.